Isothermal and differential scanning calorimetries to evaluate structural and metabolic alterations of osmo-dehydrated kiwifruit as a function of ripening stage - Panarese, Valentina (2012)
The effects of osmotic dehydration (OD) on kiwifruit outer pericarp tissue as affected by treatment extent (0-300 min) and raw kiwifruit ripening stage (9 and 14 °Bx) were investigated. Differential scanning calorimetry (DSC) measurements show decomposition of cell wall components (pectins, cellulose and hemi-celluloses). Changes in decomposition parameters (peak temperature lowered and enthalpy increased) were observed related to kiwifruit ripening degree and OD extent increased. Cell wall pectin network disassembly led to the formation of compounds with lower degradation temperature. Raw unripe fruits showed higher firmness values and lower compressibility compared to ripe and OD treated fruits. Isothermal calorimetry revealed metabolic heat production of unripe fruits decreasing linearly with the OD extent. Ripe fruit heat production sharply decreased during the first treatment hour, probably as a consequence of membrane integrity loss. Industrial relevance: OD leads to moisture removal and solute uptake in vegetable tissue, providing minimally processed commodities or ingredients for bakery or ice-cream industry. The industrial relevance is the energy-efficiency, since the process does not require water-phase change. OD provokes still unknown collateral alterations on tissue structure and metabolism. The present work applies a new calorimetric approach to evaluate both structure and metabolism changes on kiwifruit as reliant on process extent and raw fruit ripening stage.